DESKRIPSIKEMAMPUAN REPRESENTASI MATEMATISSISWA TINGKAT SMP/MTSMENGGUNAKANSOAL-SOAL TIPE PROGRAME INTERNATIONAL OF STUDENT ASSESMENT - Aisyah . (Jurnal Ilmiah Dikdaya, 2017)
Abstract : Mathematical representation is a representation, translation, disclosure, reappointment, figuratively, or modeling the idea, and the concept of mathematics contained in a configuration, construction, or certain situations shown students in various forms is an attempt to clarify the meaning of  demonstrate an understanding or seek solutions for theirs problems. This paper describes the ability of a mathematical representation of students after being given the questions of the Programe International Student Assessment (PISA) type. The subjects is students IX class of MTs PKP Al Hidayah Jambi city. While the measurement instruments is a matter of testing the ability of PISA mathematical representation type. The results showed that 96.67% of students able to present the data or information into the form of tables, charts, graphs or pictures. 80% of students can make the equation or mathematical model of the problem. 78.33% of students able to write the interpretation of the problem. 71.67% of students able to solve the problem with the steps the solving of mathematic problem.Keywords: Description, Mathematical Representation Capabilities